Modelling Numerical Simulation of DP590 Steel Undergoing Finite Strain Deformation of Uniaxial Tensile Test - mat zin, nabihah; mohd nor, mohd khir; kamarulzaman, faredzuan; abdul samad, mohd syazwan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Metal sheets made with DP steels are commonly utilized in the automobile industry to form numerous complex forms and sizes inside their products. The authors are interested in exploring the deformation behaviour of Advanced High Strength Steel (AHSS) DP 590 at various strain rates (0.0001, 0.001, 0.01 and 0.1 s−1) along two principal directions; 0° and 90°, since the material acts as an orthotropic material. The article proposed a tensile test of DP590 as to capture the deformation behaviour in terms of the stress-strain curve and perform numerical analysis by using LS Dyna FEM. The purpose of this work was to analysis the engineering data of relevant constitutive models for DP590 and to model the deformation behaviour of DP590 steel subjected to different strain rates. It is hoped that the mechanical properties of the AHSS DP590 are sensitive to the changes of the various strain rates along different principal directions. In addition, to predict the material behaviour, the material model proposed by the simplified Johnson-Cook was used.